Tourism Development Strategy for Increasing Regional Origin Income (PAD) At the Tourism Service, Buton Selatan District - Raf’ At, La Ode Muhammad Aat Affandy; Kadir, Nuraeni; Madris, Madris (International Journal of Multidisciplinary Approach Research and Science, 2023)
South Buton Regency has great potential to optimize the tourism sector. Apart from presenting stunning natural scenery, tourism also positively impacts various aspects of life, including increasing the economy through the income sector, increasing employment opportunities, promoting regional culture, and developing infrastructure. This study aims to identify strategic factors, which are strengths and weaknesses as well as opportunities and threats, and then formulate priority tourism development strategies to increase local revenue (PAD) at the South Buton Regency Tourism Office. Primary data is used through field observations and interviews, while secondary data is obtained from previous research, books, and related agencies. The results of the study indicate alternative strategies that can be considered, including increasing cultural ecotourism programs as well as improving infrastructure and marketing, promotion and awareness campaign strategies to promote South Buton Regency as an attractive tourist destination, attractions diversification strategies to attract more tourists and increase repeat visits and increase promotion through social media with an emphasis on the uniqueness of local appeal.